Network innovations: Building the next generation of agricultural scientists in Africa - Moock, Joyce Lewinger (International Food Policy Research Institute, 2016)
This chapter identifies five models of strategic networks making progress toward the stated goals of bolstering university-based training and research, and enhancing the productivity of the agricultural sector. These models, while different in their composition, offer key principles and approaches of networks that are scalable and have the potential to be sustained.2 Each model has a base secretariat or management group within a host institution that provides coordination and technical assistance, and promotes the use of low-cost (and in some cases, more advanced) information technologies. Each network is primarily based on one or more disciplinary fields, but offers an array of subject matter that encourages systems thinking; provides professional career structures necessary to develop a stable cadre of African research leaders; and creates network services that build economies of scale. These networks are fortified by linkages to local stakeholders, such as the private sector, nongovernmental organizations (NGOs), and government bodies; to continental alliances, such as the African Union (AU), Forum for Agricultural Research in Africa (FARA), and Comprehensive Africa Agriculture Development Programme (CAADP) under the auspices of the New Partnership for Africa’s Development (NEPAD); and to global agricultural entities, such as the CGIAR Consortium, world-class universities outside the region, and international markets.